Rediscovery and range extension of the rare species Diospyros truncata Zoll. & Mor. (Ebenaceae) in the State of Manipur, northeastern India - Dhatchanamoorthy, Narayanasamy; Syed, Noorinsha Begum; Lokho, Kreni; Balachandran, Natesan (Biodiversity: Research and Conservation, 2021)
Diospyros truncata Zoll. & Mor. is a rare species rediscovered in northeastern India after seven decades. A new locality of D. truncata was found in the state of Manipur, which indicates its range extension. A detailed taxonomic description, photographs and location map of this species are provided for easy identification.